THU0130 Adherence to DMARDS in Patients with Rheumatoid Arthritis - A Multicenter Outpatient Study. (10th June 2014) - Krueger, K.; Kellner, H.; Welcker, M.; Schaum, T.; Haug-Rost, I.
Abstract : Background: Due to methodological problems and definition diversities different adherence rates ranging from 49.5 - 98.5% as well as different contributing factors are found for DMARD treatment in the literature (1). Objectives: To measure adherence to MTX and other DMARDs in combination therapy in patients with rheumatoid arthritis (RA) in an outpatient setting in Germany, and to identify factors influencing adherence. Methods: In a multicentre epidemiological cross-sectional survey adult RA patients treated with MTX and at least one other DMARD for more than 6 months were questioned by a non-validated study specific questionnaire (SSQ) and a German version of the Compliance Questionnaire Rheumatology (CQR, in English validated). SSQ inquired adherence to MTX and to other self-administered DMARDs directly, asking how many of the last 20 doses were taken. Adherence was evaluated as >80% (>80% of doses reported as taken as prescribed), full (100% of doses as prescribed), and as individual rate (% of doses as prescribed). Adherence by CQR was evaluated as taking compliance >80% and CQR total score. Influencing factors were identified by a multiple regression model relating individual MTX adherence rate to predictors duration of RA, age, gender, current MTX dose, MTX route of application, duration of MTX therapy and number of concomitant DMARDs. Results: A total of 519 patients in 21 outpatient centers were included (25.0% males, 75.0% females, age 58.3±12.6 [Mean ± SD] years, RA since 11.3±8.7 years, MTX therapy since 6.9±5.0 years) with 477 returning analyzable questionnaires. 90.6 (87.6 - 93.0; 95% CI) % of patients reported >80% adherence to MTX therapy, 73.0 (68.7 - 76.9) % reported full adherence (total N =477). Mean individual adherence rate was 93.9±16.7%. Main reason for non-adherence was unintentional omission of one or more doses (16.7% of patients). Results for other self-administered DMARDs were similar, >80% adherence ranged between 82.1 (63.1 - 93.9) % for Certolizumab and 100.0 (78.2 - 100.0) % for Abatacept s.c. Adherence calculated from the CQR differed considerably (CQR taking compliance >80%: 36.3% [32.0 - 40.7] % of patients). There was nearly no agreement between CQR compliance >80% and SSQ >80% adherence to MTX (Cohen's kappa =0.007; total N =458). But there was some agreement between CQR total score (75.4±9.7; total N =499) and SSQ individual adherence rate (Spearman rank correlation =0.223; total N =458). Only influencing factors were current MTX dose ( p =0.006; patients with higher doses more adherent), and age ( p =0.017; older patients more adherent). Conclusions: Patient-reported adherence to MTX as well as other DMARD therapy is high in Germany according to SSQ. Considerable difference exists, however, between high adherence directly reported by patients (SSQ) and low adherence assessed by CQR. Factors influencing adherence to MTX therapy include current MTX dose and patients' age. Unintentional omission of doses was the main reason for non-adherence. References: Pasma A et al., Semin Arthritis Rheum 2013; 41: 18-28. Acknowledgements: This study was sponsored by an unrestricted grant by Roche. The authors determined the final content, no payments were made for writing the manuscript. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2171